Mối quan hệ phi tuyến giữa tạo thanh khoản và tỷ lệ an toàn vốn: Bằng chứng từ hệ thống ngân hàng thương mại Việt Nam - Nguyễn Thị Mỹ, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study investigates the bidirectional nonlinear relationship between liquidity creation (LC) and the capital adequacy ratio (CAR) in Vietnamese commercial banks by employing panel threshold regression (PTR) with a sample of 24 banks from 2007 to 2023. The empirical results reveal a nonlinear impact of CAR on LC and vice versa, indicating the existence of threshold effects. Specifically, when the capital adequacy ratio falls below a certain threshold, liquidity creation decreases; however, once CAR exceeds the threshold, liquidity creation increasesn. Conversely, when liquidity creation falls below its threshold, the capital adequacy ratio decreases, whereas exceeding the liquidity creation threshold leads to an increase in CAR. These findings highlight the need for policymakers to coordinate liquidity creation and capital adequacy policies to foster a sound banking system.